Diagnostic accuracy of postmortem ultrasound vs postmortem 1.5‐T MRI for non‐invasive perinatal autopsy. (1st March 2021) - Shelmerdine, S. C.; Sebire, N. J.; Arthurs, O. J.
ABSTRACT: Objectives: To determine the diagnostic accuracy of postmortem magnetic resonance imaging (PM‐MRI) and postmortem ultrasound (PM‐US) for perinatal autopsy in the same patient cohort, and to determine whether PM‐US can provide the same anatomical information as PM‐MRI. Methods: In this prospective, 5‐year (July 2014–July 2019) single‐center study, we performed 1.5‐T PM‐MRI and PM‐US in an unselected cohort of perinatal deaths. The diagnostic accuracies of both modalities were calculated, using autopsy as the reference standard. As a secondary objective, the concordance rates between the two imaging modalities for the overall main diagnosis and for five anatomical regions (brain, spine, thorax, heart and abdomen) were calculated. Results: During the study period, 136 cases underwent both PM‐US and PM‐MRI, of which 88 (64.7%) also underwent autopsy. There was no significant difference in the rates of concordance with autopsy between the two modalities for overall diagnosis (PM‐US, 86.4% (95% CI, 77.7–92.0%) vs PM‐MRI, 88.6% (95% CI, 80.3–93.7%)) or in the sensitivities and specificities for individual anatomical regions. There were more non‐diagnostic PM‐US than PM‐MRI examinations for the brain (22.8% vs 3.7%) and heart (14.7% vs 5.1%). If an 'imaging‐only' autopsy had been performed, PM‐US would have achieved the same diagnosis as 1.5‐T PM‐MRI in 86.8% (95% CI, 80.0–91.5%) of cases, with the highest rates of agreement being for spine (99.3% (95% CI, 95.9–99.9%)) and cardiac (97.3% (95% CI, 92.4–99.1%)) findings and the lowest being for brain diagnoses (85.2% (95% CI, 76.9–90.8%)). Conclusion: Although there were fewer non‐diagnostic cases using PM‐MRI than for PM‐US, the high concordance rate for overall diagnosis suggests that PM‐US could be used for triaging cases when PM‐MRI access is limited or unavailable. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.